Scoping and targeted reviews to support development of SPIRIT and CONSORT extensions for randomised controlled trials with surrogate primary endpoints: protocol. Issue 10 (13th October 2022) - Manyara, Anthony Muchai; Davies, Philippa; Stewart, Derek; Wells, Valerie; Weir, Christopher; Young, Amber; Taylor, Rod; Ciani, Oriana
Abstract : Introduction: Using a surrogate endpoint as a substitute for a primary patient-relevant outcome enables randomised controlled trials (RCTs) to be conducted more efficiently, that is, with shorter time, smaller sample size and lower cost. However, there is currently no consensus-driven guideline for the reporting of RCTs using a surrogate endpoint as a primary outcome; therefore, we seek to develop SPIRIT (Standard Protocol Items: Recommendations for Interventional Trials) and CONSORT (Consolidated Standards of Reporting Trials) extensions to improve the design and reporting of these trials. As an initial step, scoping and targeted reviews will identify potential items for inclusion in the extensions and participants to contribute to a Delphi consensus process. Methods and analysis: The scoping review will search and include literature reporting on the current understanding, limitations and guidance on using surrogate endpoints in trials. Relevant literature will be identified through: (1) bibliographic databases; (2) grey literature; (3) handsearching of reference lists and (4) solicitation from experts. Data from eligible records will be thematically analysed into potential items for inclusion in extensions. The targeted review will search for RCT reports and protocols published from 2017 to 2021 in six high impact general medical journals. Trial corresponding author contacts will be listed as potential participants for the Delphi exercise. Ethics and dissemination: Ethical approval is not required. The reviews will support the development of SPIRIT and CONSORT extensions for reporting surrogate primary endpoints (surrogate endpoint as the primary outcome). The findings will be published in open-access publications. This review has been prospectively registered in the OSF Registration DOI: 10.17605/OSF.IO/WP3QH.